Effects of a male meiotic driver on male and female transcriptomes in the house mouse. Issue 1915 (13th November 2019) - Lindholm, Anna; Sutter, Andreas; Künzel, Sven; Tautz, Diethard; Rehrauer, Hubert
Abstract : Not all genetic loci follow Mendel's rules, and the evolutionary consequences of this are not yet fully known. Genomic conflict involving multiple loci is a likely outcome, as restoration of Mendelian inheritance patterns will be selected for, and sexual conflict may also arise when sexes are differentially affected. Here, we investigate effects of the t haplotype, an autosomal male meiotic driver in house mice, on genome-wide gene expression patterns in males and females. We analysed gonads, liver and brain in adult same-sex sibling pairs differing in genotype, allowing us to identify t- associated differences in gene regulation. In testes, only 40% of differentially expressed genes mapped to the approximately 708 annotated genes comprising the t haplotype. Thus, much of the activity of the t haplotype occurs in trans, and as upregulation. Sperm maturation functions were enriched among both cis and trans acting t haplotype genes. Within the t haplotype, we observed more downregulation and differential exon usage. In ovaries, liver and brain, the majority of expression differences mapped to the t haplotype, and were largely independent of the differences seen in the testis. Overall, we found widespread transcriptional effects of this male meiotic driver in the house mouse genome.